Ritualen och dess potentiella användning i organisationer - Berglund, Erik (2007)
The essay's aim is to create an understanding for the act; ritual, and the functions or possible functions in an organisation. Many of the functions attribute to rituals lie in the ritual's double function. A ritual can function both as a practical/functional and a symbolic act. The functionality in a ritual doing is not depending of the "symbolic meaning". The functional value exists there always. The symbolic value that exists in a ritual is linked to the people's feelings and how he or she considers the ritual. This worth or symbolic function is of course different to different people and therefore the ritual influences people differently.